The fourth chronic poverty report: Growth - Andrew W. Shepherd; Katherine Bird; Lucia DaCorta; Vidya Diwakar; Amaresh Dubey; Stephen Gelb; Frederick Golooba-Mutebi; Manuela Kristin Günther; Amanda Lenhardt; Germano M. Mwabu; Lucy Scott (Overseas Development Institute (ODI), 2019)
The Chronic Poverty Report on Growth aims to put in front of economic policymakers in developing countries and international agencies evidence about the type of growth and the policies and interventions that will best allow the poor to escape poverty and stay out of it through growth. Growth does usually reduce poverty, certainly, but with much variation - from substantial impacts, through attenuated impacts - and there are also episodes where it does not, or where growth may be immiserising. The "big idea" embedded in this report is that most governments promote "growth from above", involving large, formal investments, while most people escape poverty through "growth from below", involving small, usually informal, investments by individuals and households, enabled or disadvantaged by their working environments. "Growth from below" is critical for most poor and vulnerable people but remains unrecorded and much harder to promote. Evidence from a growing database of country studies of poverty dynamics shows that most people sustaining their escapes from poverty do so through growth from below, even in countries where growth from above is generating jobs. This report analyses policies and programmatic approaches that directly help people out of poverty through the informal economy, women's economic empowerment and the inclusion of most marginalised groups, agriculture, the rural non-farm economy and migration.
Keywords: 330